2002
DOI: 10.1111/j.1552-6569.2002.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Findings of Patients With Retinal Ischemia or Embolism

Abstract: Echocardiography frequently identifies lesions of the heart or aortic arch that can act as potential sources for retinal ischemia or embolism. Further studies are needed to evaluate the prognostic and therapeutic relevance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
(9 reference statements)
0
7
0
3
Order By: Relevance
“…2 Most visible emboli are associated with internal carotid artery stenosis/occlusion, 3,4 although some can also arise from aortic arch atheroma or cardiac chambers. 5,6 Although frequently asymptomatic, retinal embolism is associated with increased mortality risk. 7,8 A few population-based studies reported retinal embolus prevalence and associated factors.…”
mentioning
confidence: 99%
“…2 Most visible emboli are associated with internal carotid artery stenosis/occlusion, 3,4 although some can also arise from aortic arch atheroma or cardiac chambers. 5,6 Although frequently asymptomatic, retinal embolism is associated with increased mortality risk. 7,8 A few population-based studies reported retinal embolus prevalence and associated factors.…”
mentioning
confidence: 99%
“…But Cardiogenic emboli are a very rare cause of CRAO. While atrial fibrillation and left ventricular dysfunction were shown to be the most common cardiac sources, extracardiac sources (mainly aortic and carotid plaques) are associated with CRAO in the large majority of patients [ 4 ]. Unfortunately, the source of embolism remains unclear in about 45 % of the patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…While atrial fibrillation and left ventricular dysfunction were shown to be the most common cardiac sources, extracardiac sources (mainly aortic and carotid plaques) are associated with CRAO in the large majority of patients. 1 Unfortunately, the source of embolism remains unclear in about 45% of the patients. 2 Other proposed mechanisms include infective endocarditis, 3 left atrial thrombosis and myxoma, 4 aortic arch atheroma, mitral annulus calcification, left atrial appendage thrombus, left atrial…”
Section: Discussionmentioning
confidence: 99%